Association Between Parental Educational Attainment and Children's Negative Urgency: Sex Differences - Shervin Assari (Shahrekord University of Medical Sciences, 2021)
Background and aims: Negative urgency reflects a specific facet of impulsivity and correlates with a wide range of health-related risk behaviors, including, but not limited to, problematic substance use. Negative urgency is also shaped by family socioeconomic position (SEP), such as parental educational attainment (PEA). This study aimed to explore sex differences regarding protective effects of PEA on children's negative urgency in the US. Methods: This cross-sectional study used the Adolescent Brain Cognitive Development (ABCD) study data. Baseline ABCD data included 10,535 American children in the age range of 9-10 years old. The independent variable was PEA, treated as a 5-level categorical variable. The primary outcome was negative urgency measured by the Urgency, Premeditation, Perseverance, Sensation Seeking, Positive Urgency, Impulsive Behavior Scale (UPPS-SS). Mixed-effects regression models were applied for data analysis. Results: In sex-stratified regression models, high PEA was predictive of lower levels of negative urgency in female but not male children. In the overall sample, sex showed a statistically significant interaction with PEA on children's negative urgency, indicating a stronger protective effect of high PEA for female compared to male children. Conclusion: PEA was a more salient determinant of negative urgency in female children than male ones. Our results also showed that American boys tend to have high levels of negative urgency, which is a risk factor of drug use, at all parental education levels.